The verses of depletion in the Holy Qur’an: a linguistic study - Jawad, Hamasat (Al-Adab Journal, 2023)
There are some verbs in the Arabic language that are similar in the number of their letters and their form, but they differ in one letter, so this simple difference leads to a difference in the pronunciation and meaning, and this is a lot in our generous Arabic language, for example our saying (Al-Nafad and Al-Nafath) and the two verbs are mentioned in four Arbitrary verses and when examining the verses of "Al-Nafad", I found that they contain phonetic, morphological, grammatical and semantic phenomena, an introduction in which I explained the meaning of Al-Nafad in language, and the difference between Al-Nafad and Al-nafath in linguistic use. The first topic was about the phonetic level, the second topic I devoted to the morphological level, and the third topic I made it about the synthetic level.